2021
DOI: 10.1155/2021/3531199
|View full text |Cite|
|
Sign up to set email alerts
|

The Influence of Different Dexmedetomidine Doses on Cognitive Function at Early Period of Patients Undergoing Laparoscopic Extensive Total Hysterectomy

Abstract: Background. This study aims to analyze the influence of different dexmedetomidine doses on cognitive function. It works on early periods of patients undergoing laparoscopic extensive total hysterectomy. Method. 119 patients with gynecological cancer underwent a laparoscopic extensive total hysterectomy. The operation was performed at the Affiliated Women’s and Children’s Hospital of Xiamen University from January 2019 to June 2020. The score of MoCA and the level of TNF-α, IL-6, S-100β protein, NSE, and GFAP o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…In addition, this procedure allows for fine observation of the lesion under laparoscopic guidance, which contributes to avoiding traumatic areas during the surgery, thus reducing the risk of disease recurrence [10] . Moreover, this procedure obviate the need to open the patient's abdomen, which effectively reduces intraoperative bleeding and the use of postoperative pain medication, thereby significantly improving the safety of the surgery [11] . However, special positions and the construction of a pneumoperitoneum are currently necessary for laparoscopic surgery, resulting in stimulation of the respiratory and cardiovascular systems and triggering a series of stress reactions [12] .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, this procedure allows for fine observation of the lesion under laparoscopic guidance, which contributes to avoiding traumatic areas during the surgery, thus reducing the risk of disease recurrence [10] . Moreover, this procedure obviate the need to open the patient's abdomen, which effectively reduces intraoperative bleeding and the use of postoperative pain medication, thereby significantly improving the safety of the surgery [11] . However, special positions and the construction of a pneumoperitoneum are currently necessary for laparoscopic surgery, resulting in stimulation of the respiratory and cardiovascular systems and triggering a series of stress reactions [12] .…”
Section: Resultsmentioning
confidence: 99%
“…In another study, dexmedetomidine was intravenously injected 10 min before anesthesia induction to 119 patients with gynecologic cancer who had undergone laparoscopic extensive hysterectomy, with a load of 1, 0.5, and 0.25µg/kg at a rate of 0.2 µg/(kg•h) until 30 minutes before the end of the operation. 0.5 µg/kg dexmedetomidine during the perianesthetic period could effectively reduce the occurrence of adverse reactions and POCD and protect brain function (Huang et al, 2021). An increasing body of evidence from recently published meta-analyses suggests that, compared with other drugs (such as sevoflurane, propofol and benzodiazepines), dexmedetomidine can improve short-term and long-term cognitive function, especially in cardiac surgery (Li M. et al, 2020;Burry et al, 2021;Xiong et al, 2021;Yu et al, 2022).…”
Section: Dexmedetomidinementioning
confidence: 99%
“…Some studies suggested that dexmedetomidine decreased the behavior of patients with postoperative cognitive dysfunction via protecting the function of nerve cells [7]. Other studies reported that dexmedetomidine did not affect the postoperative cognition in over 70-year old patients receiving elective operations [8].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggested that dexmedetomidine decreased the behavior of patients with postoperative cognitive dysfunction via protecting the function of nerve cells [ 7 ]. Other studies reported that dexmedetomidine did not affect the postoperative cognition in over 70-year old patients receiving elective operations [ 8 ]. Thus, further studies are required for evaluating the effects of dexmedetomidine on postoperative cognitive dysfunction and investigate the involved mechanisms [ 9 ].…”
Section: Introductionmentioning
confidence: 99%